The Development of Multimedia Hypermedia Applications as Evolutionary, Prototyping-Based Requirements Engineering - Sequerra-Breitman, Karin; Berry, Daniel M. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1995: Anais do IX Simpósio Brasileiro de Engenharia de Software, 1995)
It is hypothesized (1) that the problem in building multimedia hypermedia applications is that of understanding what is needed, i.e., of understanding the requirements and (2) that the development of multimedia hypermedia is essentially the engineering of requirements for one particular class of highly dynamic software-based computing systems. Moreover, because of the stability of the libraries for multimedia and hypermedia systems, the development of a prototype for validation of multimedia hypermedia requirements yields a system which is essentially of production quality. The hypothesis is supported by comparing properties of multimedia hypermedia and software systems and development in general and comparing the Hiper Autor method for multimedia hypermedia development with the spiral model for software development. Rigorous testing of the hypothesis is left for future work.